William Faulkner's The Sound and the Fury: the status of the popular in modernism - García Mainar, Luis Miguel (Revista Alicantina de Estudios Ingleses, 1999)
This paper is an attempt to assess the attitude of a modernist work towards popular culture and the social changes that transformed the United States during the twenties. Its main contention is that modernism's emphasis on epistemology has tended to obscure the conservative stance of many of its creations, apparent in their reaction against the new reconsideration of class and gender brought about by industrialisation and urbanisation. Following a combination of textual and cultural analysis, the paper scrutinises the ways in which Faulkner's The Sound and the Fury negotiates the presence of those social changes.